Effects of Nitrogen and Planting Seed Size on Cotton Growth, Development, and Yield. (1st November 2013) - Main, Christopher L.; Barber, L. Tomas; Boman, Randall K.; Chapman, Kent; Dodds, Darrin M.; Duncan, Stu; Edmisten, Keith L.; Horn, Patrick; Jones, Michael A.; Morgan, Gaylon D.; Norton, E. Randall; Osborne, Shane; et al.
Abstract : A standardized experiment was conducted during 2009 and 2010 at 20 location‐years across U.S. cotton ( Gossypium hirsutum L.)‐producing states to compare the N use requirement of contemporary cotton cultivars based on their planting seed size. Treatments consisted of three cotton varieties with planting seed of different numbers of seed per kg and N rates of 0, 45, 90, and 134 kg ha –1 . Soil at each trial location was sampled and tested for nitrate presence. High levels of soil nitrate (>91 N‐NO3 – kg ha –1 ) were found in Arizona and western Texas, and soil nitrate in the range of 45 to 73 kg N‐NO3 – ha –1 was found at locations in the central United States. Cotton lint yield responded to applied N at 11 of 20 locations. Considering only sites that responded to applied N, highest lint yields were achieved with 112 to 224 kg ha –1 of applied plus pre‐plant residual soil NO3 —translating to an optimal N requirement of 23 kg ha –1 per 218 kg bale of lint produced. Among the varieties tested those with medium‐sized seed produced higher yields in response to N than did larger and smaller seeded varieties. Varieties with larger seed had longer and stronger fibers, higher fiber length uniformity than small seeded varieties and decreased micronaire. Seed protein and oil increased and decreased slightly in response to increasing amounts of soil nitrate plus applied N, respectively.